Safety assessment of essential medicines for elderly people: a bibliographic survey - Fabiana Rossi Varallo; Fernanda Mariana de Oliveira; Patrícia de Carvalho Mastroianni (Universidade de São Paulo, 2014)
Certain medicines are considered potentially inappropriate (PIM) for elderly people as they increase the risk of adverse drug events (ADE) and because safer alternative therapies are available on the market. In this context, in order to identify the instruments that assess the quality of medical prescriptions for elderly and to determine which drugs are considered PIM, a bibliographic survey was conducted in PUBMED, LILACS and PAHO databases, in February and March/2010. The search strategy included the use of health descriptors and a manual search in the references cited by selected papers. During the period of data collection, 15 instruments were identified. In 2012, with the publication of the update of Beers criteria, this instrument was included in the study. We identified 163 PIM of 25 therapeutic classes, of which 125 (76.7%) are marketed in Brazil. Of these, 31 (24.8%) are essential medicines (RENAME 2012), of which 13 have safer therapeutic equivalents and 19 (15.2%) are over-the-counter drugs. Data suggest the need for inclusion of safer alternatives for the elderly in the national list of essential medicines and the pharmaceutical care for early detection of ADE in this age group, in order to contribute to the safe use of medicines.